Effect of workflow metrics on clinical outcomes of low diffusion-weighted imaging Alberta Stroke Program Early Computed Tomography Score (DWI-ASPECTS) patients subjected to mechanical thrombectomy. (20th November 2019) - Panni, Pietro; Michelozzi, Caterina; Richard, Sébastien; Marnat, Gaultier; Blanc, Raphaël; Consoli, Arturo; Mazighi, Mikael; Piotin, Michel; Dargazanli, Cyril; Arquizane, Caroline; Sibon, Igor; Anxionnat, René; et al.
Abstract : Background: Although accumulating evidence has demonstrated the benefit of mechanical thrombectomy (MT) in patients with low Alberta Stroke Program Early Computed Tomography Score (ASPECTS), it is still unclear how workflow metrics impact the clinical outcomes of this subgroup of patients. Methods: Patients with acute stroke and diffusion-weighted imaging (DWI) ASPECTS ≤5 at baseline, who underwent MT within 6 hours of symptoms onset, were included from a prospectively maintained national multicentric registry between January 1, 2012 to August 31, 2017. The degree of disability was assessed by the modified Rankin Scale (mRS) at 90 days. The primary outcome was functional independence defined as mRS 0 to 2 at 90 days. Results: The study included 291 patients with baseline DWI-ASPECTS ≤5. Good outcome was achieved in 82 (28.2%) patients, and 104 (35.7%) patients died within 90 days. Successful reperfusion (modified Thrombolysis In Cerebral Infarction (mTICI) 2b-3) rate was 75.3%, and median onset to recanalization (OTR) time was 2 268min. Among time-related variables, OTR emerged as the strongest predictor of primary outcome (adjusted OR for every 60 min 0.59, 95% CI 0.44 to 0.77; p<0.001). mTICI 2c-3 independently predicted a good outcome (adjusted OR 1.91, 95% CI 1.004 to 3.6; p=0.049) along with age and baseline DWI-ASPECTS. Recanalization status failed to significantly impact outcome in the DWI-ASPECTS 0–3 subpopulation. Conclusions: Near complete reperfusion (mTICI 2c-3) and OTR are the strongest modifiable outcome predictors in patients with DWI-ASPECTS ≤ 5 treated with MT.